Pulmonary Artery Thrombosis Associated with Scrub Typhus - Cho, Jeong-Hwan (Infect Chemother, 2019)
Scrub typhus is an acute febrile disease caused by Orientia tsutsugamushi, and the clinical course varies from mild and self-limiting to fatal. We describe a rare case of a pulmonary artery thrombosis associated with scrub typhus. Vasculitis via endothelial dysfunction caused by scrub typhus could be considered as the main mechanism.